China's structural adjustment from the income distribution perspective - Chong-en Bai (China Finance and Economic Review, 2015)
This paper analyzes whether China's investment and savings rates are too high by considering the rate of return to investment and other factors. It also investigates the reasons for the rapid increase in the savings rate by using various sources of data and analytical tools. In particular, much attention is paid to the distribution of income among households, corporations, and the government, and to the labor income share. Policy proposals for structural adjustment are discussed based on the finding of the investigation.
Keywords: 330; Structural imbalance; Savings rate; Investment rate; Household disposable income; The labor income share